1997
DOI: 10.3109/08860229709026265
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparative Study of Moderate Versus High Protein Intake for Critically Ill Patients with Acute Renal Failure

Abstract: Critically ill patients with acute renal failure are traditionally treated with low-protein diets to help control uremia. This dietary approach may be deleterious to the patient's nutritional status and unnecessary, especially if continuous renal placement therapies (CRRT) are used. However, the optimal amount of protein supplementation during CRRT is unknown. In patients receiving CRRT, a high protein intake may result in a positive nitrogen balance in the absence of uncontrolled uremia. Accordingly, we studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…These features permit a high protein and caloric load to compensate for the catabolic state in acute renal failure. However, studies by Bellomo et al [81] have shown that if you go up to 2.0 g/kg or 2.5 g/kg of protein loading, a positive nitrogen balance cannot be achieved and there is no additional nutritional benefit. Thus, even though CRRT permits unlimited nutritional support, there is no advantage in "overfeeding" patients.…”
Section: Dr John T Harrington (Dean Emeritus Tufts University Schomentioning
confidence: 95%
“…These features permit a high protein and caloric load to compensate for the catabolic state in acute renal failure. However, studies by Bellomo et al [81] have shown that if you go up to 2.0 g/kg or 2.5 g/kg of protein loading, a positive nitrogen balance cannot be achieved and there is no additional nutritional benefit. Thus, even though CRRT permits unlimited nutritional support, there is no advantage in "overfeeding" patients.…”
Section: Dr John T Harrington (Dean Emeritus Tufts University Schomentioning
confidence: 95%
“…Moreover, although such recommendations appear reasonable from a nitrogen-balance point of view, especially given the loss of amino acids during CRRT [21,22,23,24,25,26,27], the only randomized controlled trial focusing on clinical outcomes was conducted in 1973 [28] and has little relevance to modern practice. Moreover, recent investigations have suggested that permissive underfeeding, trophic feeding, or delayed parenteral feeding may be equivalent or perhaps superior to currently recommended approaches [29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Feinstein and colleagues (92) could not show a difference in a double-blind study that randomly assigned 30 patients with ATN to one of three isocaloric regimens: glucose alone, glucose plus essential amino acids, or glucose plus essential and nonessential amino acids. Because of the catabolic state of ATN and associated comorbid illness, a positive nitrogen balance is difficult to achieve in these patients (93,94). A recent review has recommended providing protein and nonprotein calories to meet calculated energy expenditures at a rate not to exceed 1.5 g of protein intake per kg of body weight per day in patients with ATN (95).…”
Section: Nutritional Supportmentioning
confidence: 99%